Power in the Global Era
X, 221 p.
Keywords: This volume discusses the effects of globalization on changing power relationships between transnational corporations (TNCs), and transnational capital, the state, and subnational groups. TNCs have expanded their power with the deepening of market relations, but they are not causing the state to wither away. Indeed, neoliberal changes often occur with the permission or even encouragement of powerful states. Transnational capital has weakened labour groups in order to make production more competitive, but the disadvantaged groups may mobilise to counter the power of transnational capital. Finally, globalization is subjecting domestic policies to increased international scrutiny.